Symposium on Methods of Testing Building Constructions 1962
DOI: 10.1520/stp45801s
|View full text |Cite
|
Sign up to set email alerts
|

Loading Tests on Full-Scale House Roofs

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In simulating different geometries and stiffnesses, he concluded that the deflection-based load-sharing factor varied from 8 to 40 percent depending on the ratio of rafter to batten stiffness and rafter stiffness of the rafter and load. The distributing element was also apparent in Thornburn's (1962) study. Thornburn gave no information about the stiffness of the rafters, but the relative stiffness of the 3/8-in.…”
Section: Literature Citedmentioning
confidence: 53%
See 1 more Smart Citation
“…In simulating different geometries and stiffnesses, he concluded that the deflection-based load-sharing factor varied from 8 to 40 percent depending on the ratio of rafter to batten stiffness and rafter stiffness of the rafter and load. The distributing element was also apparent in Thornburn's (1962) study. Thornburn gave no information about the stiffness of the rafters, but the relative stiffness of the 3/8-in.…”
Section: Literature Citedmentioning
confidence: 53%
“…One of the earliest studies dealing with the performance of full-scale conventional roof assemblies was conducted by Thornburn (1962). He tested a total of eight full-scale rafter roof assemblies to evaluate load capacity.…”
Section: Literature Citedmentioning
confidence: 99%
“…This conclusion has also been reached in research conducted on full-scale, wood-frame houses by Yancey [51] and Yokel [53] . "Loading Tests on Full-Scale House Roofs" [44] by H. J. Thorburn and W. R. Schriever…”
Section: Structural Evaluation Of Roofsmentioning
confidence: 99%
“…There is one feature in this evaluation that warrants consideration when developing a test method for full-scale prototype testing. The use of a whiffletree assembly to transfer the load from loading devices such as a hydraulic ram to the surface of the strucure is cited in several other reports [18] , [44] .…”
Section: S Naval Civil Engineering Research and Evaluation Laboratorymentioning
confidence: 99%